EQUITY IN THE MATHEMATICS CLASSROOM: REFLECTIONS ON INCLUSION AND TRANSFORMATIVE PEDAGOGICAL PRACTICES - dos Santos, Valéria Souza Matos; da Costa, Cleusa Vieira; da Veiga, Susana Aparecida; da Silva Richetto, Kátia Celina; Ferreira, Willian José; Silva, Tiemi Aline; Aljbaae, Samyra Faria Fontes (Seven Editora, 2025)
This study investigates the dynamics of social status in heterogeneous classrooms, focusing on the interactions that emerge during group work activities. The research is part of a master’s dissertation developed within the professional master’s program at the University of Taubaté (UNITAU), under the research line "Pedagogical Practices for Equity." It adopts a qualitative approach and aligns with Sustainable Development Goal (SDG) 4, aiming to promote quality education, especially for those who require the most support. The methodology involves the intentional formation of classroom work groups to reveal the nuances of social status among students. Inspired by the reflections of the Teacher Specialization Program (PED Brasil), the formation of random groups was designed as a methodological strategy to uncover different manifestations of social status within the school environment. During data analysis, significant dilemmas related to social status emerged, offering valuable contributions to the development of more equitable pedagogical practices. Through the proposed group work, students recognized the importance of collaboration and role-sharing, taking on responsibilities that fostered equitable participation. This allowed all students to contribute with their skills and knowledge, promoting the recognition of diversity as a pedagogical value. DOI: https://doi.org/10.56238/sevened2025.030-050